2017
DOI: 10.1016/j.cub.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Sheath Cell Invasion and Trans-differentiation Repair Mechanical Damage Caused by Loss of Caveolae in the Zebrafish Notochord

Abstract: Summary The notochord, a conserved axial structure required for embryonic axis elongation and spine development, consists of giant vacuolated cells surrounded by an epithelial sheath [1–3]. During morphogenesis, vacuolated cells maintain their structural integrity despite being under constant mechanical stress [4]. We hypothesized that the high density of caveolae present in vacuolated cells [5, 6] could buffer mechanical tension. Caveolae are 50–80 nm membrane invaginations lined by cage-like polygonal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 33 publications
9
105
0
Order By: Relevance
“…Interestingly, in migrating PGCs, Cav1-GFP is primarily localized to structures in the vicinity of the plasma membrane at the back of the migrating cells, sub-cellular localization that appeared inconsistent with a role in bleb formation (Figure S3B). Nevertheless, we proceeded to examine PGC behavior in mutant embryos lacking the maternal and zygotic of both Cav1 and Cav3 proteins, mutants in which caveolae formation and function are severely impaired, such that they are strongly reduced in number (Cao et al, 2016; Garcia et al, 2017). In these experiments, despite the lack of both caveolin proteins, we observed no effect on either bleb expansion or on the ability of the cells to actively migrate and reach their target (Figure S3C, Movie S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in migrating PGCs, Cav1-GFP is primarily localized to structures in the vicinity of the plasma membrane at the back of the migrating cells, sub-cellular localization that appeared inconsistent with a role in bleb formation (Figure S3B). Nevertheless, we proceeded to examine PGC behavior in mutant embryos lacking the maternal and zygotic of both Cav1 and Cav3 proteins, mutants in which caveolae formation and function are severely impaired, such that they are strongly reduced in number (Cao et al, 2016; Garcia et al, 2017). In these experiments, despite the lack of both caveolin proteins, we observed no effect on either bleb expansion or on the ability of the cells to actively migrate and reach their target (Figure S3C, Movie S2).…”
Section: Resultsmentioning
confidence: 99%
“…cav1;cav3 mutants fish were previously described (Cao et al, 2016; Garcia et al, 2017). Briefly, the cav1 1104 mutants were generated using TALEN pairs to target to the common sequence of both cav1 isoforms, leading to a 23nt deletion and the cav3 pd1149 mutant allele was generated using two CRISPRs that remove a 765-bp region between exon 1 and intron 1, resulting in the deletion of 90 bp of coding sequence.…”
Section: Star Methodsmentioning
confidence: 99%
“…7 There is also limited information on the function of invertebrate caveolins. 8,9,43 We also expressed a point mutant of Cav-a in a mosaic fashion in the notochord and muscle by electroporation and were able to identify a distinct phenotype, presumably as a consequence of the dominant negative effect of the mutant. The perturbation of Cav-a function by morpholino injection led to severe disruption of tail morphogenesis of Ciona embryos.…”
Section: Cav-a Is Required For the Normal Morphology Of Muscle And mentioning
confidence: 99%
“…5 Thus, they act as buffers against force to protect cells from membrane damage and loss of cell-cell contact. 8,9 At the plasma membrane, the distinctive bulb-like structure of caveolae is generated by two layers of proteins: the inner one is made up of integral membrane proteins termed caveolins, forming a putative polygonal lattice, while the outer layer comprises a filamentous coat of cavins. 7 Large numbers of caveolae are also found in the notochord of zebrafish embryos where they act as mechanoprotective agents during embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, recently showed that genetic ablation of notochordspecific cavin1b in zebrafish using CRISPR/Cas9 results in the formation of characteristic lesions in vacuolated notochord cells during development [25,33]. The zebrafish notochord plays an important role in facilitating locomotion by providing a stiff but flexible midline structure for bracing muscle contractions and is constantly exposed to mechanical stress.…”
Section: Importance Of the Uc1 Domain In Vivomentioning
confidence: 99%